ANALYSIS OF INTI - PLASMA PALM OIL PLANTATION PARTNERSHIP's PERFORMANCE IN KUANTAN SINGINGI REGION - Lukman, Indra Agus; Ismail, Munawar; -, Sasongko; Budi, Dwi (Accounting Department,, 2019)
ABSTRACT The Inti - Plasma partnership program for managing oil palm plantations in Kuantan Singingi Regency is carried out in different forms for each company and has not yet realized the roles equality of stakeholders, especially between farmers / KUD and companies. At PT. CRS and PT. SAR farmers are involved in managing farming, but at PT. TBS farmers are not involved and do not know anything about farming management. Yields and prices of Fresh Fruit Bunch (FFB) are determined unilaterally by the company. Meanwhile, the government's role is still weak for doing supervision. Such conditions create asymmetrical information and the potential for earnings management practices to harm farmers / KUD, thus weakening partnership performance and impacting the farmers’ welfare.This study aims to analyze and evaluate the performance of the Inti - Plasma partnership management of oil palm plantations in Kuantan Singingi Regency. The focus of the research is on the field research through a quantitative description analysis approach using Structural Equation Model (SEM) with the help of AMOS 2 software. Observations were made on 5 (five) latent variables namely members participation, stakeholders role, and stakeholder character as exogenous variables, as well as KUD performance and farmer welfare as endogenous variables. The indicator for each latent variable is given based on the Likert scale (1 to 5) obtained from 258 respondents, consisting of companies, banks and farmers.Based on the results of quantitative analysis showed that the model which is compiled based on theory is marginal fit, but all indicators are able to reflect the latent variables. The members participation and the role of stakeholders proved to have a significant effect on KUD performance. Thus, the performance of KUD was very significant and had a direct effect on the farmers’ welfare. Therefore, in order to improve farmers’ welfare, efforts must be made to improve the performance of KUD, especially by increasing the role of farmers and KUD as stakeholders, as well as increasing farmer participation in KUD and in farming management. Kata Kunci : Inti-Plasma partnership, asimmetrical information, KUD performance, farmers’ welfare, SEM